SUPPLY CHAIN OPERATIONAL PERFORMANCE AND ITS INFLUENTIAL FACTORS: CROSS NATIONAL COMPARISON BETWEEN JAPAN AND CHINA - Gong, Jingjing; Ogasawara, Tomohiro; Suzuki, Sadami (Brazilian Journal of Operations & Production Management, 2011)
<!–[if gte mso 9]> Normal 0 21 false false false PT-BR X-NONE X-NONE <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable mso-style-name:"Tabela normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Century","serif"; mso-ascii-font-family:Century; mso-ascii-theme-font:minor-latin; mso-hansi-font-family:Century; mso-hansi-theme-font:minor-latin; –> <!–[endif] –> This research paper is intended to investigate the supply chain operational performance and its potential factors that constitute an efficient supply chain operational performance in Japan and China. In order to perform this, the SCM logistics scorecard (LSC) has been utilized as a self-evaluation tool for participating companies. The LSC focuses on four decisive areas, namely, company strategy, planning and execution capability, logistics performance, and IT method and implementation. The number of participating companies was 554 from Japan and 236 from China. The scores in each assessment area were compared between the two countries. Subsequently, factor analysis has been conducted by using the result of LSC in order to identify the significant factors which established the operational performance of SCM in each country. The result of the factor analysis indicated that the structure in generating successful SCM in Japanese industry and the Chinese were considered similar in the aspect of SCM realization, SCM strategy and the utilization of IT along the chain. Finally, the correlation between extracted factors and financial bottom lines was conducted, which indicated that improving SCM performance brought positive impact on financial outcome, especially when IT utilization in cooperation with SCM organization strategy.